2019
DOI: 10.1016/j.omtn.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Viral Vector-Based Delivery of CRISPR/Cas9 and Donor DNA for Homology-Directed Repair in an In Vitro Model for Canine Hemophilia B

Abstract: Gene therapy represents an attractive alternative to treat hemophilia B. Here we established three hepatocyte-derived cell lines based on Huh7, PLC/PRF/5, and Hep3B cells stably carrying a mutated canine FIX (cFIXmut) transgene containing a single point mutation in the catalytic domain. Based on these in vitro models resembling a commonly used canine large animal model, the tetracycline-controlled transcriptional activator (Tet-on)-inducible CRISPR/Cas9 system and an optimized donor were used to correct mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…It can be programmed to target any genomic locus followed by a 5 0 -protospacer adjacent motif sequence of NGG, with the specificity determined by the sgRNA containing a 20-nt guide sequence complementary to the genome locus of interest [92,93]. In addition to our work with ZFNs, TALENs, and CRISPR/Cas9 expressed from HDAd5/35 vectors [52,53,55,103], many other research groups have demonstrated successful genomic editing using Ad vectors, including HDAd, expressing CRISPR/Cas9 [104][105][106][107][108][109]. Moreover, a variety of Cas9 derivatives and orthologs have been developed, for instance, CRISPRa [96], Cpf1 [97], saCas9 [98], and Cas13 [99] to name a few.…”
Section: Site-specific Dna Breaks Mediated By Endonucleasesmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be programmed to target any genomic locus followed by a 5 0 -protospacer adjacent motif sequence of NGG, with the specificity determined by the sgRNA containing a 20-nt guide sequence complementary to the genome locus of interest [92,93]. In addition to our work with ZFNs, TALENs, and CRISPR/Cas9 expressed from HDAd5/35 vectors [52,53,55,103], many other research groups have demonstrated successful genomic editing using Ad vectors, including HDAd, expressing CRISPR/Cas9 [104][105][106][107][108][109]. Moreover, a variety of Cas9 derivatives and orthologs have been developed, for instance, CRISPRa [96], Cpf1 [97], saCas9 [98], and Cas13 [99] to name a few.…”
Section: Site-specific Dna Breaks Mediated By Endonucleasesmentioning
confidence: 99%
“…Three of these trials sponsored by different companies have reached Phase III [two for hemophilia B (NCT03861273 and NCT03569891); one for hemophilia A (NCT03370913)] [16]. Efficient targeted integration of a F9 gene was also demonstrated by using a single HDAd vector simultaneously carrying CRISPR/Cas9 and a donor cassette [105]. However, the widespread application of existing rAAV-based approach could face several obstacles: (a) mostly episomal nature of rAAV genomes affecting durability of efficacy, specifically in children with actively dividing hepatocytes (patients under 18 years old are excluded by most of current gene therapy trials); (b) the high cost of rAAV vector production, estimated to be > $1 M per patient; (c) the limited packaging capacity of rAAV which cannot accommodate large transcriptionally regulatory elements (viral titer drops precipitously with transgenes > 5 kb); and (d) the pre-existing immunity to AAV capsid leads to loss of efficacy and circumvents repeated administration (subjects with pre-existing antibodies to the used rAAV serotype are not eligible for current clinical trials) [228].…”
Section: Hemophiliamentioning
confidence: 99%
See 2 more Smart Citations
“…Cas9) function in mammalian cells, many strategies have been devised that exploit their reprogrammable capacity for inducing double-strand breaks (DSBs) for performing gene editing. This includes delivering donor sequences via AdV/AAV, highyield PCR product, plasmid, or single stranded DNA oligonucleotides, and Cas/CRISPR components via plasmid, RNA, RNP, or replication-incompetent viruses (Jin et al 2019;Ehrke-Schulz et al 2017;Mangeot et al 2019;Liu et al 2018;Gao et al 2018;Moore et al 2015;Tálas et al 2017). In addition to targeted gene editing for fixing germ-line mutation diseases, the current "killer app" for inserting synthetic transgenes is CAR-T, whereby T cells are programmed to target cancer cells using an engineered chimeric antigen receptor (CAR) (Bloemberg et al 2019).…”
Section: Introductionmentioning
confidence: 99%